Diagnóstico del Nivel de Capacitación del Personal Vinculado al Sector Siderúrgico y Metalmecánico de Boyacá respecto a las Normas de Competencia Laboral - Carreno-Bodensiek, Carlos Guillermo; González-Calixto, Mónica Bibiana; Patarroyo-Durán, Nubia Isolina (Revista Científica, 2016)
This work presents the results of a research process applied to a sample of companies in the steel and metalworking sector in Boyacá, Colombia. The active workers are evaluated over the Occupational Competency Standards related to their daily activities. It also aims to highlight the formation priority of human talent for business, according to build up a level of competitiveness. Also, seeks to meet the need to train and develop skills and competencies in the workforce, taking into account the concepts of experts about training and developing proposals for management. This research is consistent with global trends in education and the requirements of standardization of training, why diagnoses and designs are focused on the functions of the companies related to the Standards of Competency.